Conceptualising the FinDD API plug-in: A study of BIM-FM integration - Pärn, E.A.; Edwards, D.J. (Automation in construction, 2017)
This research paper reports upon a client driven approach to iteratively develop the FinDD application programming interface (API) plug-in. FinDD integrates building information modelling (BIM) and facilities management (FM) via the novel development and application of totems. Totems visualise rich semantic FM data in a 3D object to extend the use and application of COBie thereby minimising costs incurred by the FM team to update and maintain the as-built BIM. Participatory action research was used to develop the proof of concept and involved a study of two multi-storey, mixed-use educational buildings (with a contract value worth ≥£150 million UK Sterling) located within Birmingham, UK. The lead researcher worked for the client's estates department and was instrumental in liaising with members of the project management team, synthesising their semantic data requirements and developing the FinDD API plug-in for Autodesk Revit. Research findings reveal that whilst FinDD was positively received as a bespoke extension of COBie (that was tailored to specifically meet client needs), further development is required to mitigate software inflexibility and augment automation of semantic data transfer, storage and analysis. Future work will validate the API plug-in via user experience and integrate additional databases such as post occupancy evaluations (POE). •A bespoke application programming interface (API) for BIM-FM integration is presented.•Totems developed visualise rich semantic FM data in 3D objects.•User group feedback provided guidance on the API's functionality.•Standard COBie data drops are challenged and future work is proposed. [Display omitted]